2009
DOI: 10.1080/10463280902860037
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of lay epistemics: The why, how, and who of knowledge formation

Abstract: A conceptual integration and review are presented of three separate research programmes informed by the theory of lay epistemics (Kruglanski, 1989). They respectively address the owhyo, ohowo, and owhoo questions about human knowledge formation. The owhyo question is treated in work on the need for cognitive closure that propels epistemic behaviour and affects individual, interpersonal, and group phenomena. The ohowo question is addressed in work on the unimodel (Kruglanski, Pierro, Mannetti, Erb, Chun, 2007) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 68 publications
3
119
1
8
Order By: Relevance
“…derived from his early writings, similar definitions and objections can be found in the author's much later works (e.g., Kruglanski, 2004;Kruglanski, Dechesne, Orehek, & Pierro, 2009;Roets, Kruglanski, Kossowska, Pierro, & Hong, 2015). This proves that the possibility of motivation to avoid closure is a consistently formulated theoretical postulate.…”
Section: From the Need For Closure Avoidance To The Need For Closurementioning
confidence: 93%
See 1 more Smart Citation
“…derived from his early writings, similar definitions and objections can be found in the author's much later works (e.g., Kruglanski, 2004;Kruglanski, Dechesne, Orehek, & Pierro, 2009;Roets, Kruglanski, Kossowska, Pierro, & Hong, 2015). This proves that the possibility of motivation to avoid closure is a consistently formulated theoretical postulate.…”
Section: From the Need For Closure Avoidance To The Need For Closurementioning
confidence: 93%
“…As evidenced by the summarized results, although in most cases the need for closure speeds up and simplifies the process of formulating knowledge (review: Kruglanski et al, 2009), situations in which individuals characterized by a strong motivation to achieve closure are ready to make extra cognitive effort in order to formulate a credible answer to a persistent question are not only possible in theory but also observable in practice. The above results are derived from a wide variety of studies, their topics extend over subjects such as abstract problems (Jaśko et al, 2015), consumer decisions (Houghton & Grewal, 2000), and actual behavior in a social context (Kosic et al, 2004).…”
Section: The Dual Consequences Of the Need For Closure And The Need Tmentioning
confidence: 99%
“…Most people are quite good at the task of evaluating the best argument, both at the individual and group level, when motivated to do so. When held accountable under a time pressure, however, people exhibit the primacy effect, giving more weight to information they received first (Kruglanski, et al, 2009). …”
Section: §322 Accuracy and Accountabilitymentioning
confidence: 99%
“…Furthermore, we are susceptible to all sorts of biases that make knowing difficult. For example, we tend to favor evidence or data received early in our inquiries (Kruglanski, Dechesne, Orehek, & Pierro, 2009) and we tend to discount the weight of evidence that counts against hypotheses we endorse (Nickerson, 1998). Second, evolutionary psychologists have offered some intriguing arguments that these dispositions are embedded within our cognitive architecture in ways that can systematically lead us to biased thinking, in some cases for adaptive reasons (Mercier & Sperber, 2011).…”
mentioning
confidence: 99%
“…The need for completion is theoretically continuous and focuses on the diagnostic knowledge and stereotypical judgment rather than the prototype to trigger decreased processing of knowledge and increasing judicial confidence, as well as increasing identification (1). In addition, the need for closure is associated with time pressure, physical discomfort, or situations in which a clear decision is needed and with many psychosocial variables (21). For example, it was found that individuals with low need for closure had flexible thinking, took longer to decide, and had greater tolerance for ambiguity (8,22).…”
mentioning
confidence: 99%